A method for longitudinal, transcranial imaging of blood flow and remodeling of the cerebral vasculature in postnatal mice. Issue 12 (18th December 2014) - Letourneur, Annelise; Chen, Victoria; Waterman, Gar; Drew, Patrick J.
Abstract In the weeks following birth, both the brain and the vascular network that supplies it undergo dramatic alteration. While studies of the postnatal evolution of the pial vasculature and blood flow through its vessels have been previously done histologically or acutely, here we describe a neonatal reinforced thin‐skull preparation for longitudinally imaging the development of the pial vasculature in mice using two‐photon laser scanning microscopy. Starting with mice as young as postnatal day 2 (P2), we are able to chronically image cortical areas >1 mm2, repeatedly for several consecutive days, allowing us to observe the remodeling of the pial arterial and venous networks. We used this method to measure blood velocity in individual vessels over multiple days, and show that blood flow through individual pial venules was correlated with subsequent diameter changes. This preparation allows the longitudinal imaging of the developing mammalian cerebral vascular network and its physiology.